The Impact of FDI on Economic Development of Pakistan - Mahmood, Muhammad Tahir (Journal of Social and Development Sciences, 2012)
The foreign direct investment has made its position better as a bundle of benefits during the last three decades at the global level. The ultimate result of its benefits for the recipient countries is often sought in term of economic development. Such results do not appear in the same fashion in all recipient economies and so provide the space to investigate this nexus at country level. This study is an endeavor to examine empirically the impact of FDI on economic development of Pakistan. For this purpose, the time series data covering the period (1971-2009) were used. For data analysis, the bound testing approach to co integration within the framework of the Autoregressive Distributed Lag (ARDL) was utilized. The findings of the study supported the hypothesis of positive impact of FDI on economic development of Pakistan. The results also endorsed the views that the FDI is more effective than that of domestic investment.